Peran Good Corporate Governance dalam Memoderasi Pengaruh Penghindaran Pajak dan Profitabilitas Pada Nilai Perusahaan - Putu, Sisilia Dewi; Hasibuan, Henny Triyana (E-Jurnal Akuntansi; Vol 32 No 10 (2022)DO - 10.24843/EJA.2022.v32.i10.p15, 2022)
The purpose of this study was to determine the effect of tax avoidance and profitability on firm value with good corporate governance (GCG) as a moderating variable. The observed companies are manufacturing companies listed on the Indonesia Stock Exchange in 2018-2020. The number of samples used in the study were 77 companies with purposive sampling technique. The data analysis technique used is moderated regression analysis (MRA). The results showed that tax avoidance had no effect on firm value and good corporate governance (GCG) was unable to moderate the effect of tax avoidance on firm value. The study also found that profitability had a positive effect on firm value and good corporate governance (GCG) was able to strengthen the influence of profitability on firm value. Keywords: Firm Value; Good Corporate Governance; Profitability, Tax Avoidance.